A PRELIMINARY STUDY ON SUPERSTIMULATORY RESPONSE USING LOW DOSE FSH AND SUBSEQUENT EMBRYO TRANSFER IN SAHIWAL CATTLE DURING SUMMER SEASON - SINGHAL, S; SINGH, N; MALIK, VS; KUMAR, A; BRAR, PS (The Indian Journal of Animal Reproduction, 2017)
The superstimulation of two elite Sahiwal donors using 200 mg Follicle Stimulating Hormone (FSH, total dose) yielded on an average 21 follicles with ovulation of 18 follicles and recovery of nine embryos per cattle. Following transfer of eight fresh embryos in seven surrogate cattle, four became pregnant (pregnancy rate, 57.14%). Thus, FSH @ 200 mg can be used for superstimulation associated with fresh embryo transfer in Sahiwal cattle during summer season.
Keywords: Conception rate; FSH; Sahiwal; Summer; Superstimulatory response